Cultivo de postlarvas de paco Piaractus brachypomus, Cuvier 1818. (Serrasalmidae), bajo tres densidades de siembra en un sistema de recirculación acuícola, Banda de Shilcayo, San Martín - Coral Cashú, Braian Harry (2022)
The present investigation evaluated the effects of three stocking densities of postlarvae (pl) of paco Piaractus brachypomus (Cuvier, 1818) 10 days after the hatching of the DPE, in an aquaculture recirculation system (RAS), for 35 days. The investigation consisted of 3 treatments and 3 repetitions (T1: 1pl / liter, T2: 3pl / liter and T3: 5pl / liter), distributed in a completely randomized design (DCA). The food was constituted in 2 stages: 1st stage: Live food + Commercial food + Additive; 2nd stage: Commercial feed + Additive, from which the growth in weight and length, the zootechnical indices and the water quality parameters are evaluated. Growth was recorded every 17 days, parameters such as temperature, pH, dissolved oxygen and oxygen saturation were analyzed daily, while alkalinity, ammonia, nitrites and nitrates were analyzed weekly. The results indicate that in the growth of weight and length; increased weight and length; Specific growth rate and condition factor were not recorded significant differences between treatments, however, survival indicates better performance in T1 where a significant difference (p> 0.05) is recorded between treatments. The water quality parameters did not present sudden oscillations that would have generated adverse conditions for the cultivation of paco Piaractus brachypomus postlarvae, the biological filter kept the toxic metabolites stable during the experimentation period. Finally, it was possible to produce pieces of commercial weight and size in an aquaculture recirculation system, while the low survival values indicate that the stocking density does not have a direct relationship on the behavior of the postlarvae, including the quality of the water. and the Bioavailability of live food essential for the cultivation of paco Piaractus brachypomus in its first stages.